High-wear-resistance copper-based active brazing filler metal for superhard abrasive particles, preparation method and brazing method

By adding iron, nickel, silicon, manganese and other elements to CuSnTi brazing, forming micro-nano hard particles, the problem of poor wear resistance of the brazing material is solved, and the wear resistance and hardness of the brazing material and the brazing alloy are significantly improved. Meet the processing needs of high efficiency, high speed and heavy load.

CN119237988APending Publication Date: 2025-01-03HENAN MECHANICAL & ELECTRICAL VOCATIONAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411483660.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing CuSnTi brazing material has problems of low strength and toughness and poor wear resistance during use, especially after brazing diamond, the hardness of the brazing seam layer is low and the wear resistance is poor, making it difficult to meet the processing needs of high efficiency, high speed and heavy loads.

Method used

By adding iron, nickel, silicon, manganese and other elements to CuSnTi brazing, and controlling the component ratio and brazing process, dispersed distribution of micro-nano hard particles are formed, so as to achieve fine crystal strengthening and solidification of the brazing material and its brazing stitch alloy. The solvent strengthening and the second phase strengthening avoid or reduce the generation of CuSn3Ti5 phase and improve the wear resistance of solder and brazing stitch alloy.

Benefits of technology

It significantly improves the hardness and wear resistance of copper-based active brazing, meets the processing performance requirements of high efficiency, high speed and heavy loads, and reduces the melting temperature of the brazing alloy, prevents the formation of CuSn3Ti5 phase, and improves the resistance of the brazing stitch alloy. Abrasiveness and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237988A_ABST
    Figure CN119237988A_ABST
Patent Text Reader

Abstract

The invention discloses high-wear-resistance copper-based active brazing filler metal for superhard abrasive particles. The high-wear-resistance copper-based active brazing filler metal comprises, by weight, 5-18 parts of nickel, 7-12 parts of tin, 8-15 parts of titanium, 1-3 parts of gallium, 1-5 parts of germanium, 1-5 parts of iron, 0.5-5 parts of manganese, 0.5-2 parts of silicon, 0.01-0.1 part of rare earth and the balance copper. The brazing method of the brazing filler metal comprises the steps that the high-abrasion-resistance copper-based active brazing filler metal is laid on the to-be-welded face of the steel base body, the super-hard abrasive is arranged on the high-abrasion-resistance copper-based active brazing filler metal, a brazing assembly is obtained, and brazing of the super-hard abrasive is obtained after brazing in a vacuum furnace and heat preservation aging treatment are adopted. The obdurability and wear resistance of the copper-tin-titanium brazing filler metal and the brazing gold thereof are improved by avoiding or reducing the formation of a thick CuSn3Ti5 phase in the copper-tin-titanium brazing filler metal and the brazing gold thereof, regulating and controlling the form and size of the phase, eliminating or reducing the deterioration influence of the phase on the wear resistance of the brazing filler metal, adding nickel, iron, silicon and manganese elements and controlling the component proportion and the brazing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing, and in particular to a highly wear-resistant copper-based active brazing filler metal for superhard abrasive particles, a preparation method and a brazing method. Background Art

[0002] Diamond has extremely high hardness and excellent wear resistance, which determines that it is an ideal abrasive for manufacturing brittle material processing tools, and enjoys the reputation of "industrial teeth". Brazed diamond tools have high service life and processing efficiency due to the characteristics of high abrasive connection strength, high exposure, and controllable arrangement. They can meet the processing needs of high efficiency, high speed, and heavy loads, and are widely used in oil drilling, geological exploration, stone processing, building decoration and other fields. Therefore, economical and high-performance brazed diamond abrasives have become a research hotspot at home and abroad.

[0003] Due to the large interfacial energy difference between diamond and metal, the brazing filler metal usually contains certain active elements such as Ti, Cr, Zr and V. During the brazing process, carbide layers such as TiC, Cr2C3, and VC are formed on the surface of diamond by means of the chemical metallurgical reaction between the active brazing filler metal and diamond, so that the brazing filler metal alloy can firmly hold the diamond abrasive grains. Therefore, the brazing filler metal containing active elements such as Ti, Cr, Zr and V is called active brazing filler metal. At present, the active brazing fillers on the market mainly include NiCrBSi active brazing filler metal, AgCuTi active brazing filler metal and CuSnTi active brazing filler metal. Compared with NiCrBSi active brazing filler metal and AgCuTi active brazing filler metal, CuSnTi active brazing filler metal has a moderate melting temperature, less thermal effect on diamond, reduces the graphitization tendency of diamond, has low production cost, and has good economic efficiency, so it has attracted much attention. However, due to the limitations of the composition design of CuSnTi brazing filler metal, its microstructure is mainly composed of α-Cu solid solution and a large amount of coarse and brittle CuSn3Ti5 phase. Among them, the coarse CuSn3Ti5 phase is extremely brittle and can be broken by a small external force, which significantly deteriorates the wear resistance of the brazing alloy. Since most of the Sn and Ti elements in the CuSnTi brazing filler metal form a coarse and brittle CuSn3Ti5 phase, and the amount of solid solution in the α-Cu solid solution is small, the solid solution strengthening effect on the α-Cu solid solution is small, resulting in low hardness of the α-Cu solid solution. Therefore, the CuSnTi brazing filler metal has technical difficulties such as low toughness and poor wear resistance during use, which is very inconsistent with the wear resistance of super-hard abrasives such as diamond. Especially after brazing diamond, the brazing seam layer has low hardness and poor wear resistance. It is very easy to be worn by the chips of the processed materials such as ceramics, granite, and stone during use, causing the brazing alloy support arm holding the diamond to be quickly worn away, resulting in the diamond falling off, making it difficult to meet the processing requirements of high efficiency, high speed, and heavy load, limiting its promotion and application. Therefore, it is necessary to reasonably design the composition and content ratio of CuSnTi solder to improve the strength of α-Cu solid solution, avoid the formation of CuSn3Ti5 phase, or strictly control the content, morphology and size of CuSn3Ti5 phase.

[0004] The prior art discloses a powdered active brazing filler metal for diamond abrasive tools. The powdered active brazing filler metal includes, by mass percentage, 55-70% Cu, 12-18% Sn, 3-10% Al, 1-10% Zn, 5-10% Ti, 1-6% Si and 0.01-3% Ni. The brazing filler metal disclosed in the technology is a copper-tin-titanium active brazing filler metal with composite additions of aluminum, zinc, silicon and nickel. The obtained brazing filler metal alloy has a low melting temperature and a low melting point for diamond. Under the multiple effects of the solid solution strengthening effect of aluminum and nickel elements and the active element titanium, the active brazing filler metal alloy can form a firm metallurgical bond between the diamond and the substrate when brazing the diamond and the substrate. However, the disclosed solder composition contains 12-18% Sn and 5-10% Ti. Within this composition range, a large amount of coarse CuSn3Ti5 phases are inevitably formed in the solder, making it difficult to improve the wear resistance of the solder. In addition, the disclosed solder composition contains 1-10% Zn. As is known to all, the boiling point of Zn in the atmosphere is low, and the Zn element is oxidized in the atmosphere and in a high vacuum (no higher than 5×10 -2 In the environment of Pa, Zn element is very volatile. Although it is mentioned that Si can prevent the volatilization of Zn element, in fact, within the composition range of this technology, Si preferentially reacts with Ti to produce Si3Ti5 phase, which makes it difficult to effectively prevent the volatilization of Zn element.

[0005] A copper-based active solder is disclosed in which active elements such as nickel, chromium, and phosphorus are added to a copper-tin-titanium-based alloy, wherein the weight percentage of each active element is 52% to 68% copper, 17% to 23% tin, 5% to 11% titanium, 5% to 9% nickel, 3% to 5% chromium, and 0.5% to 1.5% phosphorus. The obtained active solder has the characteristics of low brazing temperature, good wettability, strong gap filling ability, and high wear resistance. However, the disclosed solder composition contains 17% to 23% tin and 5% to 11% titanium, and the added nickel, chromium, and phosphorus have low affinity for tin and titanium, and have little effect on each other. Therefore, within this composition range, a large amount of coarse CuSn3Ti5 phases are still inevitably formed in the solder, making it difficult to significantly improve the wear resistance of the solder.

[0006] Also disclosed is a copper-tin-titanium solder whose main components are Cu, Sn and Ti. A large amount of coarse CuSn3Ti5 phase is still inevitably formed in the copper-tin-titanium solder, making it difficult to improve the wear resistance of the solder. In addition, the disclosed forming method of the solder involves an electroplating process, which is not conducive to green environmental protection.

[0007] Other prior arts disclose methods of regulating the performance of copper-tin-titanium solder from different aspects, but the main components of the solder involved are still Cu, Sn, and Ti, and a large amount of coarse CuSn3Ti5 phases are still inevitably formed in the solder, and the technical problem of low wear resistance of the solder has not been solved. Summary of the invention

[0008] In order to overcome the above shortcomings, the present invention provides a highly wear-resistant copper-based active solder for superhard abrasive particles and a brazing method thereof, aiming to avoid or reduce the formation of coarse CuSn3Ti5 phases in the copper-tin-titanium solder and its brazing alloy, and regulate the morphology and size of the CuSn3Ti5 phases in the copper-tin-titanium solder and its brazing alloy, and eliminate or reduce the deteriorating effect of the CuSn3Ti5 phase on the wear resistance of the solder; at the same time, by compositely adding nickel, iron, silicon, and manganese elements, and controlling the component ratio and brazing process, the synergistic strengthening of the solder and its brazing alloy through fine grain strengthening, solid solution strengthening, and second phase strengthening is achieved, and the strength, toughness, and wear resistance of the copper-tin-titanium solder and its brazing alloy are significantly improved.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is: A highly wear-resistant copper-based active brazing filler metal for superhard abrasive grains comprises the following elemental components by weight: 5 to 18 parts of nickel, 7 to 12 parts of tin, 8 to 15 parts of titanium, 1 to 3 parts of gallium, 1 to 5 parts of germanium, 1 to 5 parts of iron, 0.5 to 5 parts of manganese, 0.5 to 2 parts of silicon, 0.01 to 0.1 parts of rare earth, and the balance is copper; the above components are respectively present in the form of copper-nickel alloy, copper-tin alloy, copper-titanium alloy, copper-manganese alloy, copper-silicon alloy, copper-gallium alloy, copper-germanium alloy, copper-iron alloy and copper-rare earth alloy; The rare earth is a mixture of cerium and yttrium, and the weight ratio of cerium to yttrium is 1:5-8.

[0010] The weight ratio of manganese to silicon is 1:0.5-5.

[0011] The method for preparing a highly wear-resistant copper-based active brazing filler metal for superhard abrasive grains comprises the following steps: Step 1, according to the weight of each component, copper-nickel alloy, copper-tin alloy, copper-titanium alloy, copper-gallium alloy, copper-germanium alloy, copper-iron alloy, copper-manganese alloy, copper-silicon alloy and copper rare earth alloy are weighed, and each of the weighed metal alloys is ultrasonically cleaned with acetone solution and ultrasonically cleaned with alcohol solution in turn, the acetone solution ultrasonic cleaning is 10 to 20 minutes, and the alcohol ultrasonic cleaning is 5 to 10 minutes. After the ultrasonic cleaning is completed, the alloy is taken out and dried with cold wind for later use; Step 2: placing the copper-nickel alloy, copper-tin alloy, copper-silicon alloy and copper-iron alloy weighed in step 1 into a magnesium oxide crucible in an induction melting furnace, and performing induction melting in an atmospheric environment. After each metal alloy is completely melted, stirring with a dry wooden stick to mix the components evenly to obtain alloy liquid A. During the induction melting process, the metal alloy is covered with activated carbon powder; Step 3, putting the copper-gallium alloy, copper-germanium alloy and copper-rare earth alloy weighed in step 1 into the alloy liquid A obtained in step 2, adjusting the induction heating power to completely melt the copper-gallium alloy, copper-germanium alloy and copper-rare earth alloy, and stirring with a dry wooden stick to evenly mix the components to obtain alloy liquid B; Step 4: adding the copper-manganese alloy and copper-titanium alloy weighed in step 2 to the alloy liquid B obtained in step 3, adjusting the induction heating power to completely melt the copper-manganese alloy and copper-titanium alloy, and stirring with a dry wooden stick to evenly mix the components to obtain alloy liquid C; Step 6, adding an activator and a refining agent to the alloy liquid C obtained in step 4, and at the same time covering the surface of the alloy liquid C with a thick layer of activated carbon powder, and blowing high-purity argon gas for stirring to fully refine the liquid alloy, and keeping it at 950-1050°C for 3-10 min to complete the smelting of the solder alloy, and obtain the highly wear-resistant copper-based active solder ingot for the superhard abrasive grains; The refining agent comprises 30% to 45% by mass of cryolite and 55% to 70% by mass of boric anhydride; The active agent comprises 66% to 77% by mass of boric anhydride, 12% to 19% by mass of dehydrated borax and 10% to 15% by mass of calcium fluoride; The gas pressure of the high-purity argon gas is lower than the pressure when the turbulent alloy liquid is about to blow away the covering activated carbon powder; Step 7: Use a conventional copper roller rotating strip-spinning device to prepare the highly wear-resistant copper-based active solder ingot obtained in step 6 into a thin strip of highly wear-resistant copper-based active solder.

[0012] The method for brazing superhard abrasives using the superhard abrasive grains with high wear-resistant copper-based active brazing filler metal comprises the following steps: S1. Degrease the super-hard abrasive, rinse it with distilled water, activate it and rinse it with distilled water in sequence, grind the steel substrate to be welded to a metallic luster, wipe it with alcohol, blow it dry and set it aside; S2, laying the highly wear-resistant copper-based active brazing filler metal on the to-be-welded surface of the steel substrate treated in S1, and then placing the superhard abrasive cleaned in S1 on the highly wear-resistant copper-based active brazing filler metal to obtain a brazed assembly; S3. Braze the brazed assembly obtained in S2 by brazing in a vacuum furnace. After brazing, cool to 380-420 °C for heat preservation and aging treatment. The aging treatment insulation time is 100-140 min. After the aging treatment, cool to room temperature to complete the brazing of the superhard abrasive.

[0013] Further optimization, the distilled water rinsing in S1 is to put the superhard abrasive into distilled water and ultrasonically clean it until it is neutral; the activation is to put the superhard abrasive into 5-10% nitric acid solution or sulfuric acid solution for ultrasonic activation at room temperature for 8-10 minutes.

[0014] Further optimization, in step S1, the size of the steel substrate is Ф10×40mm-Ф6×20mm, the surface to be welded is an end face with a size of Ф6×20mm at one end and a side face with a length of 10mm close to the end face, and the surface to be welded is polished by one of machining, angle grinder polishing, sandpaper polishing, sand blasting, and shot peening.

[0015] Further optimization, in step S2, the size of the end face solder sheet is Φ6×0.2 mm, and the size of the side face solder sheet is 18.8×0.2 mm.

[0016] Further optimization, in step S1, the superhard abrasive grain is one of diamond and cubic boron nitride.

[0017] Further optimization, in step S2, the highly wear-resistant copper-based active brazing filler metal and the super-hard abrasive grains are fixed by a glue carrier.

[0018] Further optimization, the brazing process parameters in the vacuum furnace in step S3 are: the vacuum degree in the vacuum furnace is ≤5×10 -3 MPa, the brazing temperature is 880-950 ℃, and the holding time at the brazing temperature is 3-10 min; during the heating process, the heating rate from room temperature to 500 ℃ is 10-15 ℃ / min, and the temperature is kept at 500 ℃ for 5-10 min, and the heating rate from 500 ℃ to the brazing temperature is 5 ℃ / min; during the cooling process, it is furnace cooled from the brazing temperature to the aging temperature, and after the aging treatment, it is furnace cooled to 100 ℃, and then taken out and naturally cooled to room temperature.

[0019] Further optimization, in step S3, the brazing method adopts one of vacuum induction brazing, high-purity argon protection induction brazing, and high-purity argon protection laser brazing.

[0020] The beneficial effects of the present invention are: (1) The highly wear-resistant copper-based active solder of the present invention is based on the Cu-Sn-Ti solder, and iron is added to react with titanium in the Cu-Sn-Ti solder to generate FeTi compounds, thereby avoiding or reducing the formation of coarse, hard, brittle and easy-to-crack CuSn3Ti5 phases in the solder and solder joint alloy, optimizing the microstructure of the solder and solder joint alloy, and eliminating or reducing the deterioration effect of the coarse CuSn3Ti5 phase on the wear resistance of the solder and solder joint alloy; (2) The present invention adds strengthening elements such as nickel, silicon, manganese and rare earth elements (Ce and Y) in combination, rationally designs the composition control factors of the manganese / silicon weight ratio and the cerium / yttrium weight ratio, and combines the aging treatment after brazing to form dispersed (Mn, Ni)5Si3, (Mn, Fe, Ni)5Si3 and other micro-nano hard particles in the brazing filler metal and the brazing seam alloy, which play a second phase strengthening role on the α-Cu matrix phase in the brazing filler metal and the brazing seam alloy, and significantly improve the microhardness and wear resistance of the brazing filler metal and the brazing seam alloy; wherein the yttrium element absorbs oxygen in the liquid brazing filler metal to form nano yttrium oxide particles, increasing the (Mn, Ni)5Si3, The number of non-uniform nucleation and precipitation of second phase particles such as (Mn,Fe,Ni)5Si3, manganese and iron elements regulate the lateral growth of (Mn,Ni)5Si3 and (Mn,Fe,Ni)5Si3 particles, silicon elements promote the longitudinal growth of (Mn,Ni)5Si3 and (Mn,Fe,Ni)5Si3 particles, and nickel elements inhibit the longitudinal growth of (Mn,Ni)5Si3 and (Mn,Fe,Ni)5Si3 particles. Therefore, the present invention reasonably designs the component ratio, effectively controls the growth morphology of micro-nano particles, enables it to exert the maximum second phase strengthening effect, and improves the wear resistance of solder and soldering alloy; (3) Since the iron element causes the melting temperature of the solder to increase, the added iron content cannot be too high. In order to prevent the remaining Ti from reacting with iron and continuing to react with Sn to form CuSn3Ti5 phase, the present invention adds gallium, germanium, manganese and other melting-reducing elements to replace part of the tin and reduce the tin content, which not only reduces the melting temperature of the solder, but also prevents the formation of large blocks or long strips of CuSn3Ti5 phase in the solder and the soldering alloy; (4) The present invention also adds rare earth cerium and nickel in combination. Cerium can refine grains and purify grain boundaries. By rationally designing the component control factor of the cerium / yttrium mass ratio, the effects of cerium and yttrium in the solder are distinct. Yttrium can better absorb oxygen in the liquid solder to form nano yttrium oxide particles as heterogeneous nucleation cores. Nickel is infinitely miscible with copper and forms a continuous solid solution with copper, having a large range of single-phase regions, and having a good solid solution strengthening effect on the α-Cu matrix phase. (5) It can be seen from the beneficial effects of (1) to (4) above that the solder composition designed by the present invention, in combination with the brazing process and aging treatment, actually performs a comprehensive synergistic strengthening method of second phase strengthening, solid solution strengthening and fine grain strengthening on the solder and the brazing alloy, which can significantly improve the hardness and wear resistance of the copper-based active solder, and the brazed superhard tool meets the requirements of high-efficiency, high-speed and heavy-load processing performance; (6) The vacuum furnace brazing process provided by the present invention has strong reliability and high yield rate. After brazing, the superhard abrasive tool has good macroscopic morphology, the superhard abrasive particles have little thermal damage, high edge sharpness and low shedding rate, the brazing alloy has good wettability to the superhard abrasive, and the brazed alloy has good wear resistance.

[0021] (7) The method for preparing the highly wear-resistant copper-based active solder provided by the present invention does not require the use of vacuum equipment and can realize the preparation of the active solder in an atmospheric environment. The oxidation of the Ti element is a major breakthrough in the field of active solder preparation. The process is simple, the operation is convenient, and the cost is low, providing a new technical approach for the preparation of other active solders. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The highly wear-resistant copper-based active solder prepared by the present invention; Figure 2 The microstructure of the solder alloy of Example 1 of the present invention; Figure 3 The microstructure of the solder alloy of Comparative Example 1 of the present invention; Figure 4 This is the macroscopic morphology of the brazed diamond grinding head of Example 1 of the present invention; Figure 5 The friction and wear test results of the brazed joint of Example 2 of the present invention are shown; Figure 6 The friction and wear test results of the brazed joint of Example 3 of the present invention are shown; Figure 7 The friction and wear test results of the brazed joint of Comparative Example 1 of the present invention are as follows; Figure 8 Schematic diagram of the steel substrate structure used in Examples 1-3 and Comparative Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0023] In order to more clearly understand the above-mentioned purposes, features and advantages of the present invention, the present invention is described in detail below in conjunction with specific embodiments. The following embodiments are implemented based on the technical solutions of the present invention, and detailed implementation methods and specific operating procedures are given. However, the present invention can also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the following embodiments.

[0024] Example 1 A highly wear-resistant copper-based active brazing filler metal for super-hard abrasive grains, the highly wear-resistant copper-based active brazing filler metal for super-hard abrasive grains comprising the following elemental components by weight: 12 parts of nickel, 8 parts of tin, 8 parts of titanium, 1 part of gallium, 1 part of germanium, 5 parts of iron, 1 part of manganese, 0.5 parts of silicon, 0.02 parts of rare earth, and the balance being copper; Preferably, when weighing the copper alloy raw materials of each elemental component, the burn-up rate of each elemental component should be considered. The burn-up rate of each elemental component under vacuum melting furnace conditions is: 1wt.% copper, 1.5wt.% nickel, 1.5wt.% tin, 2wt.% titanium, 2.5wt.% manganese, 6wt.% silicon, 1wt.% gallium, 1wt.% germanium, 0.5wt.% iron, and 0.2wt.% rare earth.

[0025] Preferably, the rare earth is a mixture of cerium and yttrium, and the weight ratio of cerium to yttrium is 1:5.

[0026] Preferably, the nickel, tin, titanium, manganese, silicon, germanium, gallium, iron and rare earth element components exist in the form of copper-nickel alloy, copper-tin alloy, copper-titanium alloy, copper-manganese alloy, copper-silicon alloy, copper-gallium alloy, copper-germanium alloy, copper-iron alloy and copper-rare earth alloy, respectively.

[0027] The method for preparing a highly wear-resistant copper-based active brazing filler metal for superhard abrasive grains comprises the following steps: Step 1, according to the weight proportions of the above components, copper-nickel alloy, copper-tin alloy, copper-titanium alloy, copper-gallium alloy, copper-germanium alloy, copper-iron alloy, copper-manganese alloy, copper-silicon alloy and copper-rare earth alloy are weighed, and the weighed metal alloys are ultrasonically cleaned with acetone solution and ultrasonically cleaned with alcohol solution in turn, the acetone solution ultrasonic cleaning is for 15 min, the alcohol ultrasonic cleaning is for 8 min, and after the ultrasonic cleaning is completed, the mixture is taken out and dried with cold wind for later use; Step 2: placing the copper-nickel alloy, copper-tin alloy, copper-silicon alloy and copper-iron alloy weighed in step 1 into a magnesium oxide crucible in an induction melting furnace, and performing induction melting in an atmospheric environment. After each metal alloy is completely melted, stirring with a dry wooden stick to mix the components evenly to obtain alloy liquid A. During the induction melting process, the metal alloy is covered with activated carbon powder; Step 3, putting the copper-gallium alloy, copper-germanium alloy and copper-rare earth alloy weighed in step 1 into the alloy liquid A obtained in step 2, adjusting the induction heating power to completely melt the copper-gallium alloy, copper-germanium alloy and copper-rare earth alloy, and stirring with a dry wooden stick to evenly mix the components to obtain alloy liquid B; Step 4: adding the copper-manganese alloy and copper-titanium alloy weighed in step 2 to the alloy liquid B obtained in step 3, adjusting the induction heating power to completely melt the copper-manganese alloy and copper-titanium alloy, and stirring with a dry wooden stick to evenly mix the components to obtain alloy liquid C; Step 6: adding an activating agent and a refining agent to the alloy liquid C obtained in step 4, and at the same time covering the surface of the alloy liquid C with a thick layer of activated carbon powder, and blowing high-purity argon gas for stirring to fully refine the liquid alloy, and keeping it at 1000°C for 5 minutes to complete the smelting of the solder alloy, and obtain the highly wear-resistant copper-based active solder ingot for the superhard abrasive grains; The refining agent comprises 40% by mass of cryolite and 60% by mass of boric anhydride, and the activating agent comprises 70% by mass of boric anhydride, 15% by mass of dehydrated borax and 15% by mass of calcium fluoride; The gas pressure of the high-purity argon gas is lower than the pressure when the turbulent alloy liquid is about to blow away the covering activated carbon powder; Step 7: Use a conventional copper roller rotating strip-spinning device to prepare the highly wear-resistant copper-based active solder ingot obtained in step 6 into a thin strip of highly wear-resistant copper-based active solder.

[0028] A method for brazing superhard diamond abrasive grains using highly wear-resistant copper-based active brazing filler metal comprises the following steps: S1. Place the diamond abrasive in a 5 g / L NaOH solution for ultrasonic degreasing for 15 min, then place it in distilled water for ultrasonic cleaning for 20 min, wash it with distilled water until it is neutral, then place it in a 5% nitric acid solution for ultrasonic activation at room temperature for 10 min, and finally place it in distilled water for ultrasonic cleaning for 20 min. After washing it with distilled water until it is neutral, take it out and dry it at 50°C for use; S2. Select a steel substrate made of 45# steel and a part to be brazed of 6×10 mm in size. Use metallographic sandpaper to polish the steel substrate, especially the surface to be brazed, until the surface has a metallic luster. Then, place it in an alcohol solution for ultrasonic cleaning for 5 min and blow dry for later use. S3, brushing a glue carrier on the surface to be brazed of the steel substrate treated in step S2, and spreading the high wear-resistant copper-based active brazing filler metal on the surface to be brazed of the steel substrate through the glue carrier, and then discharging the diamond abrasive cleaned in step 1 on the high wear-resistant copper-based active brazing filler metal spread on the surface to be brazed of the steel substrate through the glue carrier to obtain a brazed assembly; brazing the brazed assembly obtained in step 3 by brazing in a vacuum furnace, cooling to 400°C after brazing for heat preservation and aging treatment, the heat preservation time of the aging treatment is 120 min, cooling to 100°C after the aging treatment, taking out and naturally cooling to room temperature to complete the brazing of the diamond grinding head.

[0029] Preferably, in S3, the brazing process parameters in the vacuum furnace are: the vacuum degree in the vacuum furnace is ≤5×10 -3 MPa, the brazing temperature is 900 ℃, and the holding time at the brazing temperature is 5 min; during the heating process, the heating rate from room temperature to 500 ℃ is 10 ℃ / min, and it is kept at 500 ℃ for 5 min, and the heating rate from 500 ℃ to the brazing temperature is 5 ℃ / min; during the cooling process, it is furnace cooled when the brazing temperature reaches the aging temperature (400 ℃), and after the aging treatment, it is furnace cooled to 100 ℃, and then taken out and naturally cooled to room temperature.

[0030] Example 2 The difference between this embodiment and Example 1 is that the copper alloy raw material of each elemental component is weighed according to the following weight proportions: 15 parts of nickel, 9.5 parts of tin, 11 parts of titanium, 2 parts of gallium, 3 parts of germanium, 3 parts of iron, 2 parts of manganese, 1.5 parts of silicon, 0.05 parts of rare earth, and the balance is copper; the preparation method of the high wear-resistant copper-based active solder for superhard abrasive grains is the same as that in Example 1, and the method of brazing diamond abrasive grains with the high wear-resistant copper-based active solder is the same as that in Example 1.

[0031] Example 3 The difference between this embodiment and Example 1 is that the copper alloy raw material of each elemental component is weighed according to the following weight proportions: 18 parts of nickel, 12 parts of tin, 15 parts of titanium, 3 parts of gallium, 5 parts of germanium, 5 parts of iron, 4 parts of manganese, 2 parts of silicon, 0.1 parts of rare earth, and the balance is copper; the preparation method of the high wear-resistant copper-based active solder for superhard abrasive grains is the same as that in Example 1, and the method of brazing diamond abrasive grains with the high wear-resistant copper-based active solder is the same as that in Example 1.

[0032] Comparative Example 1 A highly wear-resistant copper-based active brazing filler metal for super-hard abrasive grains, the highly wear-resistant copper-based active brazing filler metal for super-hard abrasive grains comprising the following elemental components by weight: 12 parts of nickel, 8 parts of tin, 8 parts of titanium, 1 part of gallium, 1 part of germanium, 1 part of manganese, 0.5 parts of silicon, 0.02 parts of rare earth, and the balance of copper; Preferably, when weighing the copper alloy raw materials of each elemental component, the burn-up rate of each elemental component should be considered. The burn-up rate of each elemental component under vacuum melting furnace conditions is: 1wt.% copper; 1.5wt.% nickel; 1.5wt.% tin; 2wt.% titanium; 2.5wt.% manganese; 6wt.% silicon; 1wt.% gallium; 1wt.% germanium; 0.2wt.% rare earth.

[0033] The preparation method of the highly wear-resistant copper-based active solder for the superhard abrasive grains is the same as that in Example 1.

[0034] A method for brazing superhard diamond abrasive grains using highly wear-resistant copper-based active brazing filler metal comprises the following steps: S1. Place the diamond abrasive in a 5 g / L NaOH solution for ultrasonic degreasing for 15 min, then place it in distilled water for ultrasonic cleaning for 20 min, wash it with distilled water until it is neutral, then place it in a 5% nitric acid solution for ultrasonic activation at room temperature for 10 min, finally place it in distilled water for ultrasonic cleaning for 20 min, wash it with distilled water until it is neutral, then take it out and dry it at 50°C for use; S2. Select a steel substrate made of 45# steel and a part to be brazed of 6×10 mm in size. Use metallographic sandpaper to polish the steel substrate, especially the surface to be brazed, until the surface has a metallic luster. Then, place it in an alcohol solution for ultrasonic cleaning for 5 min and blow dry for later use. S3, brushing a glue carrier on the surface to be brazed of the steel substrate treated in step 2, and spreading the high wear-resistant copper-based active brazing filler metal on the surface to be brazed of the steel substrate through the glue carrier, and then discharging the diamond abrasive cleaned in step 1 on the high wear-resistant copper-based active brazing filler metal spread on the surface to be brazed of the steel substrate through the glue carrier to obtain a brazed assembly; brazing the brazed assembly obtained in step 3 by brazing in a vacuum furnace, cooling to 400°C for heat preservation and aging treatment after brazing, the heat preservation time of the aging treatment is 120 min, cooling to 100°C after the aging treatment, taking out and naturally cooling to room temperature to complete the brazing of the diamond grinding head.

[0035] Preferably, in S3, the brazing process parameters in the vacuum furnace are: the vacuum degree in the vacuum furnace is ≤5×10 -3 MPa, the brazing temperature is 900 ℃, and the holding time at the brazing temperature is 5 min; during the heating process, the heating rate from room temperature to 500 ℃ is 10 ℃ / min, and it is kept at 500 ℃ for 5 min, and the heating rate from 500 ℃ to the brazing temperature is 5 ℃ / min; during the cooling process, it is furnace cooled when the brazing temperature reaches the aging temperature (400 ℃), and after the aging treatment, it is furnace cooled to 100 ℃, and then taken out and naturally cooled to room temperature.

[0036] Comparative Example 2 The difference between this embodiment and Example 1 is that the copper alloy raw material of each elemental component is weighed according to the following weight proportions: 12 parts of nickel, 8 parts of tin, 8 parts of titanium, 1 part of gallium, 1 part of germanium, 5 parts of iron, 0.02 parts of rare earth, and the balance is copper; the preparation method of the highly wear-resistant copper-based active brazing material for superhard abrasives is the same as that in Example 1, and the method of brazing diamond abrasives is the same as that in Example 1.

[0037] Comparative Example 3 The difference between this embodiment and Example 1 is that when the high wear-resistant copper-based active brazing filler metal is used to braze diamond abrasive grains, no aging treatment is performed during the cooling process after brazing. Instead, the brazing is directly cooled to 100°C in the furnace after brazing, and then taken out and naturally cooled to room temperature to complete the brazing of the diamond grinding head. The preparation method of the high wear-resistant copper-based active brazing filler metal for superhard abrasive grains is the same as that of Example 1, and the method of brazing diamond abrasive grains is the same as that of Example 1.

[0038] Comparative Example 4 The difference between this embodiment and Example 1 is that the copper alloy raw material of each element component is weighed according to the following weight parts: 12 parts of nickel, 8 parts of tin, 8 parts of titanium, 1 part of gallium, 1 part of germanium, 5 parts of iron, 5 parts of manganese, 0.5 parts of silicon, 0.02 parts of rare earth, and the balance is copper. The preparation method of the highly wear-resistant copper-based active brazing material for superhard abrasive grains is the same as that of Example 1, and the method of brazing diamond abrasive grains is the same as that of Example 1.

[0039] The performance of the brazing materials and the brazed diamond samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested, and the test results are as follows: 1. Microstructure Figure 2 The microstructure of the solder alloy of Example 1 is shown in FIG. Figure 3 The microstructure of the solder alloy of comparative example 1. It can be seen that no iron element is added to the solder of comparative example 1, and a large number of coarse CuSn3Ti5 phases are formed in the solder. An appropriate amount of iron element is added in Example 1, which significantly refines the solder microstructure, transforms the coarse CuSn3Ti5 phase into a fine CuSn3Ti5 phase that is close to equiaxed, thereby eliminating or reducing the deterioration effect of the coarse CuSn3Ti5 phase on the wear resistance of the solder and the solder joint alloy. At the same time, a large number of small-particle FeTi compounds are formed in the solder of Example 1, which can improve the wear resistance of the solder.

[0040] 2. Performance Testing The shear strength and microhardness test methods of the high wear-resistant copper-based active solder are conventional mechanical properties test methods; the solder layer wear test method is as follows: first, the solder prepared in Examples 1 to 3 and Comparative Examples 1 to 4 is used to vacuum-clad the solder layer on the surface of the steel substrate, and aging treatment is performed according to Examples 1-3 and Comparative Examples 1-4, and the solder layer is taken out after cooling to room temperature, and then the clad solder layer is machined to make the clad solder layer smooth and flat. As the friction object, the friction pair is silicon carbide ceramic, and the friction and wear test is performed on a friction and wear testing machine. The spindle speed is 500 r / min, the grinding pressure is 600N, and the friction time is 5 min. The amount of solder layer removed per unit time is used as an indicator for evaluating the wear resistance of the solder layer. The results are shown in Table 1.

[0041] The performance of the brazed diamond grinding head is mainly processing efficiency, effective grinding life and diamond shedding rate. The performance data such as processing efficiency, effective grinding life and diamond shedding rate can be obtained by friction and wear test of the diamond grinding head. The friction and wear test process of the diamond grinding head is as follows: the grinding tool is the brazed diamond grinding head prepared by Examples 1 to 3 and Comparative Examples 1 to 4, the workpiece material to be ground is SiC ceramic, the spindle speed is 1000 r / min, and the grinding pressure is 600 N. During the grinding test, if the grinding head slips obviously, or starts to vibrate violently, or the grinding distance does not change for a long time, it is considered that the grinding head cannot work. The total effective grinding time of the diamond grinding head is used to characterize its effective grinding life, and the removal amount of the workpiece to be ground per unit time is used to characterize the processing efficiency, and the number of diamond particles before and after the diamond grinding head is ground is counted, and the diamond shedding rate is calculated by "(the number of diamond particles before grinding-the number of diamond particles after grinding) / the number of diamond particles before grinding", and the results are shown in Table 1.

[0042] In summary, the high wear-resistant copper-based active solder and its brazing method provided by the present invention, the high wear-resistant copper-based active solder layer has high shear strength and microhardness, and its wear resistance is much greater than that of comparative examples 1-4. The diamond grinding head brazed with the high wear-resistant copper-based active solder has good processing efficiency and service life.

[0043] Table 1 The above shows and describes the main features, methods of use, basic principles and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements according to actual conditions, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. Highly wear-resistant copper-based active brazing filler metal for super-hard abrasive grains, characterized in that: The composition comprises the following elements by weight: 5 to 18 parts of nickel, 7 to 12 parts of tin, 8 to 15 parts of titanium, 1 to 3 parts of gallium, 1 to 5 parts of germanium, 1 to 5 parts of iron, 0.5 to 5 parts of manganese, 0.5 to 2 parts of silicon, 0.01 to 0.1 parts of rare earth, and the balance is copper; the above components exist in the form of copper-nickel alloy, copper-tin alloy, copper-titanium alloy, copper-manganese alloy, copper-silicon alloy, copper-gallium alloy, copper-germanium alloy, copper-iron alloy and copper-rare earth alloy respectively; The rare earth is a mixture of cerium and yttrium, and the weight ratio of cerium to yttrium is 1:5-8.

2. The highly wear-resistant copper-based active brazing filler metal for superhard abrasive grains according to claim 1, characterized in that: The weight ratio of manganese to silicon is 1:0.5-5.

3. The method for preparing the highly wear-resistant copper-based active brazing filler metal for superhard abrasive grains according to claim 1-2, characterized in that: The following steps are involved: Step 1, according to the weight of each component, copper-nickel alloy, copper-tin alloy, copper-titanium alloy, copper-gallium alloy, copper-germanium alloy, copper-iron alloy, copper-manganese alloy, copper-silicon alloy and copper rare earth alloy are weighed, and each of the weighed metal alloys is ultrasonically cleaned with acetone solution and ultrasonically cleaned with alcohol solution in turn, the acetone solution ultrasonic cleaning is 10 to 20 minutes, and the alcohol ultrasonic cleaning is 5 to 10 minutes. After the ultrasonic cleaning is completed, the alloy is taken out and dried with cold wind for later use; Step 2: placing the copper-nickel alloy, copper-tin alloy, copper-silicon alloy and copper-iron alloy weighed in step 1 into a magnesium oxide crucible in an induction melting furnace, and performing induction melting in an atmospheric environment. After each metal alloy is completely melted, stirring with a dry wooden stick to mix the components evenly to obtain alloy liquid A. During the induction melting process, the metal alloy is covered with activated carbon powder; Step 3, putting the copper-gallium alloy, copper-germanium alloy and copper-rare earth alloy weighed in step 1 into the alloy liquid A obtained in step 2, adjusting the induction heating power to completely melt the copper-gallium alloy, copper-germanium alloy and copper-rare earth alloy, and stirring with a dry wooden stick to evenly mix the components to obtain alloy liquid B; Step 4: adding the copper-manganese alloy and copper-titanium alloy weighed in step 2 to the alloy liquid B obtained in step 3, adjusting the induction heating power to completely melt the copper-manganese alloy and copper-titanium alloy, and stirring with a dry wooden stick to evenly mix the components to obtain alloy liquid C; Step 6, adding an activator and a refining agent to the alloy liquid C obtained in step 4, and at the same time covering the surface of the alloy liquid C with a thick layer of activated carbon powder, and blowing high-purity argon gas for stirring to fully refine the liquid alloy, and keeping it at 950-1050°C for 3-10 min to complete the smelting of the solder alloy, and obtain the highly wear-resistant copper-based active solder ingot for the superhard abrasive grains; The refining agent comprises 30% to 45% by mass of cryolite and 55% to 70% by mass of boric anhydride; The active agent comprises 66% to 77% by mass of boric anhydride, 12% to 19% by mass of dehydrated borax and 10% to 15% by mass of calcium fluoride; The gas pressure of the high-purity argon gas is lower than the pressure when the turbulent alloy liquid is about to blow away the covering activated carbon powder; Step 7: Use a conventional copper roller rotating strip-spinning device to prepare the highly wear-resistant copper-based active solder ingot obtained in step 6 into a thin strip of highly wear-resistant copper-based active solder.

4. The method for brazing superhard abrasives using the highly wear-resistant copper-based active brazing filler metal for superhard abrasives as claimed in claim 1, characterized in that: The following steps are involved: S1. Degrease the super-hard abrasive, rinse it with distilled water, activate it and rinse it with distilled water in sequence, grind the steel substrate to be welded to a metallic luster, wipe it with alcohol, blow it dry and set it aside; S2, laying the highly wear-resistant copper-based active brazing filler metal on the to-be-welded surface of the steel substrate treated in S1, and then placing the superhard abrasive cleaned in S1 on the highly wear-resistant copper-based active brazing filler metal to obtain a brazed assembly; S3. Braze the brazed assembly obtained in S2 by brazing in a vacuum furnace. After brazing, cool to 380-420 °C for heat preservation and aging treatment. The aging treatment insulation time is 100-140 min. After the aging treatment, cool to room temperature to complete the brazing of the superhard abrasive.

5. The method for brazing superhard abrasives using the highly wear-resistant copper-based active brazing filler metal as claimed in claim 4, characterized in that: The distilled water rinsing in S1 is to put the superhard abrasive into distilled water and ultrasonically clean it until it becomes neutral; the activation is to put the superhard abrasive into 5-10% nitric acid solution or sulfuric acid solution for ultrasonic activation at room temperature for 8-10 minutes.

6. The method for brazing superhard abrasives using the highly wear-resistant copper-based active brazing filler metal as claimed in claim 4, characterized in that: In step S1, the size of the steel substrate is Φ10×40mm-Φ6×20mm, the surface to be welded is an end surface with a size of Φ6×20mm at one end and a side surface with a length of 10mm close to the end surface, and the surface to be welded is polished by machining, angle grinder polishing, sandpaper polishing, sandblasting, and shot peening; In the step S2, the size of the end face solder sheet is Φ6×0.2 mm, and the size of the side face solder sheet is 18.8×0.2 mm.

7. The method for brazing superhard abrasives using the highly wear-resistant copper-based active brazing filler metal as claimed in claim 4, characterized in that: In the step S1, the superhard abrasive grain is one of diamond and cubic boron nitride.

8. The method for brazing superhard abrasives using the highly wear-resistant copper-based active brazing filler metal as claimed in claim 4, characterized in that: In the step S2, the highly wear-resistant copper-based active solder and the super-hard abrasive grains are fixed by means of a glue carrier.

9. The method for brazing superhard abrasives using the highly wear-resistant copper-based active brazing filler metal as claimed in claim 4, characterized in that: The brazing process parameters in the vacuum furnace in step S3 are: the vacuum degree in the vacuum furnace is ≤5×10 -3 MPa, the brazing temperature is 880-950 ℃, and the holding time at the brazing temperature is 3-10 min; during the heating process, the heating rate from room temperature to 500 ℃ is 10-15 ℃ / min, and the temperature is kept at 500 ℃ for 5-10 min, and the heating rate from 500 ℃ to the brazing temperature is 5 ℃ / min; during the cooling process, it is furnace cooled from the brazing temperature to the aging temperature, and after the aging treatment, it is furnace cooled to 100 ℃, and then taken out and naturally cooled to room temperature.

10. The method for brazing superhard abrasives using the highly wear-resistant copper-based active brazing filler metal as claimed in claim 4, characterized in that: The brazing method in step S3 is one of vacuum induction brazing, high-purity argon protection induction brazing, and high-purity argon protection laser brazing.